The first three terms for the expression 2n-6 are obtained by substituting n with consecutive integers. When n=1, the expression evaluates to -4; when n=2, the expression evaluates to -2; and when n=3, the expression evaluates to 0. Therefore, the first three terms are -4, -2, and 0.
Oh, what a happy little question we have here! The first three terms for 2n-6 would be 2n-6, 2n, and 2n+6. Just remember, there are no mistakes in math, only happy little accidents.
They are: -4, -2 and 0
The first three terms for the expression 2n-1 can be found by substituting n with the first three consecutive integers. When n=1, the expression becomes 2(1)-1 = 1. When n=2, the expression becomes 2(2)-1 = 3. When n=3, the expression becomes 2(3)-1 = 5. Therefore, the first three terms are 1, 3, and 5.
29
You use the FOIL method. First terms Outer terms Inner terms Last terms.
What is the sum of the first 27 terms of the geometric sequence -3, 3, - 3, 3, . . . ?
First off, it is NOT A QUINTIC! Typically a polynomial of four or more terms is called "a polynomial of n terms", where n is the number of terms. Only the one, two, and three term polynomials are referred to by a particular naming convention.
Which sequence? Oh, that one! The first three terms are 1, 2 and 72.
3 7 11
To find the first 5 terms, plug 1, 2, 3, 4 and 5 in for n:3*1-3 = 03*2-3 = 33*3-3 = 63*4-3 = 93*5-3 = 12The first five terms are 0, 3, 6, 9 and 12.
it is 8.
4, 8, 12
3
n = 1 ---> 3 * 1 + 3 = 6 n = 2 ---> 3 * 2 + 3 = 9 first 2 have difference of 3, so you can keep adding 3 to find more terms. 6, 9, 12, 15
The first three terms for the expression 2n-1 can be found by substituting n with the first three consecutive integers. When n=1, the expression becomes 2(1)-1 = 1. When n=2, the expression becomes 2(2)-1 = 3. When n=3, the expression becomes 2(3)-1 = 5. Therefore, the first three terms are 1, 3, and 5.
The first four terms are 3 9 27 81 and 729 is the 6th term.
Suppose the first term is a, the second is a+r and the nth is a+(n-1)r. Then the sum of the first five = 5a + 10r = 85 and the sum of the first six = 6a + 15r = 123 Solving these simultaneous equations, a = 3 and r = 7 So the first four terms are: 3, 10, 17 and 24
5
3, 15, 75, 375